Forensics for Dummies - Lyle, D. P. (Hoboken, N.J. : Wiley, 2004)
'Forensics for Dummies' looks at the methods used by police and other professionals to evaluate evidence gathered at a crime scene and ultimately identify the victim, criminal, circumstances and cause of death.
Includes index.
Keywords: Forensic sciences -- Popular works; Crime